Certain aspects of the systemic etiopathogenesis of dystrophic-inflammatory periodontal diseases (a literature review) - O. M. Nemesh; Z. M. Honta; I. V. Shylivskyi; K. A. Moroz; O. O. Myhal (Zaporožskij Medicinskij Žurnal)
Aim. To study the main pathogenetic mechanisms in the development of dystrophic-inflammatory periodontal diseases by analyzing scientific research results covered in current specialized literature.